2017
DOI: 10.1177/0269881117725683
|View full text |Cite
|
Sign up to set email alerts
|

Reward-related limbic memory and stimulation of the cannabinoid system: An upgrade in value attribution?

Abstract: While a lot is known about the mechanisms promoting aversive learning, the impact of rewarding factors on memory has received comparatively less attention. This research investigates reward-related explicit memory in male rats, by taking advantage of the emotional-object recognition test. This is based on the prior association, during conditioned learning, between a rewarding experience (the encounter with a receptive female rat) and an object; afterwards rat discrimination and recognition of the 'emotional ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Furthermore, since dysfunctions of the synaptic triad amongst glutamate, GABA and DA in the mesocorticolimbic regions have long been implicated in the underlying pathogenesis of alcohol use disorders (Cannizzaro et al, 2019;Spiga et al, 2014), it is reasonable to suggest that the augmented operant behaviour for alcohol observed in this study can result from prenatal THCinduced aberrant plasticity in specific areas of the brain that are functionally associated with reward, motivation and salience attribution (Brancato et al, 2014(Brancato et al, , 2018bCannizzaro et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, since dysfunctions of the synaptic triad amongst glutamate, GABA and DA in the mesocorticolimbic regions have long been implicated in the underlying pathogenesis of alcohol use disorders (Cannizzaro et al, 2019;Spiga et al, 2014), it is reasonable to suggest that the augmented operant behaviour for alcohol observed in this study can result from prenatal THCinduced aberrant plasticity in specific areas of the brain that are functionally associated with reward, motivation and salience attribution (Brancato et al, 2014(Brancato et al, , 2018bCannizzaro et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…Consistently, prenatal exposure to cannabinoids induces subtle yet persisting changes in cognitive functions that emerge when cognitive abilities require emotional integration (Bara et al, 2018; Mereu et al, 2003; Morena et al, 2015). Indeed, whereas activation of CB1 receptors within the mPFC strongly potentiates normally non-salient emotional memory formation (Brancato et al, 2018b; Laviolette and Grace, 2006; Tan et al, 2014), THC administration alters facial recognition (Hindocha et al, 2015), decreases, in the Amy, blood oxygen level–dependent response to threatening faces (Phan et al, 2008) and preferentially impairs memory for emotional events in humans (Ballard et al, 2013). The mechanisms by which CB1 transmission regulates emotional memory formation are not entirely understood, but a single systemic stimulation of the cannabinoid transmission by the CB1 agonist WIN 55, 212-2 decreases limbic memory in the same Emotional Object Recognition task in adult rats (Brancato et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that disrupting OFC function abolished control of discrimination accuracy by signaled reward probability in our task ( Ward et al, 2015b ; Hall-McMaster et al, 2017 ) similarly to what we found here. Finally, other signaling pathways in the BF-prefrontal circuit, such as the endocannabinoid system, have recently been identified as important in BF modulation of cortical activity and in the processing of reward-driven motivational salience ( Llorente-Ovejero et al, 2017 ; Brancato et al, 2018 ). Clearly, further work that delineates the specific neural populations and timecourse of neural activity involved in SPSA performance is needed in order to clarify the specific role of cholinergic and non-cholinergic BF projections neurons and other circuitry in the effects seen here.…”
Section: Discussionmentioning
confidence: 99%
“…The limbic system, in particular the amygdala and hippocampus, by supporting the formation of associative memory, promotes positive and negative reinforcement of rewards including those of substances of abuse (58). Indeed, animal models demonstrate memory performance to not only be dependent on emotional processes, but may be modulated by augmentation of ECS signaling (5962). Phytocannabinoids, such as THC and CBD for example have been found to modulate brain activity level across limbic regions during emotional processing tasks (63, 64).…”
Section: Ecs Role In Substance Use Disorder (Sud)mentioning
confidence: 99%